The 1 mg overnight dexamethasone suppression test: a danger to the adrenal gland?. Issue 4 (August 2022) - Vanek, Chaim; Loriaux, Lynn
Abstract : Purpose of review: The 1 mg overnight dexamethasone suppression test (ONDST) with a cutoff cortisol value of 1.8 mcg/dl (50 nmol/l) is routinely used for the assessment of incidental, benign adrenal nodules. Patients with an abnormal test are diagnosed with mild autonomous cortisol secretion (MACS). This timely commentary reviews the origins of the ONDST, its relationship to the diagnoses of MACS, and whether this is clinically relevant for clinical care. Recent findings: Millions of incidental adrenal nodules are found on CT scans annually. Several papers in the last three years discuss and advocate for the diagnose of MACS via the ONDST. Summary: An ONDST cutoff of 1.8 mcg/dl (50 nmol/l) in patients with no clinical features of Cushing's syndrome will produce false positive results and a diagnosis of MACS that could result in unnecessary adrenalectomy.